BASIC COMPUTER AND MICROSOFT OFFICE APPLICATION TRAINING FOR SCHOOL-AGED CHILDREN IN PASIR GALA VILLAGE, LAWE BULAN DISTRICT, SOUTHEAST ACEH REGENCY - Jiwa Malem Marsya (Jurnal Pengabdian Bangsa, 2026)
The objectives of this basic computer training are: To introduce participants to the importance of mastering information technology and Computers today and to teach them how to use Microsoft Word applications, which can be used for learning to type and other purposes. The method used in this activity is Community Education (PKM) in the form of lectures and training on the basics of computers and Microsoft Office applications, specifically Microsoft Word. The result of this PkM activity is to provide implications for increasing participants' knowledge about computers and their applications to young children in the village of Pasir Gala, Lawe Bulan District, Southeast Aceh Regency.